THE PROTECTION OF FOSSILS IN BADEN-WÜRTTEMBERG (FEDERAL REPUBLIC OF GERMANY) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2004)
In Baden-Württemberg, fossils of special scientific and public interest have been protected as cultural monuments by the Monument Protection Law since 1972. Two areas of outstanding importance, Holzmaden and Nusplingen, are declared Protected Excavation Area. Other important permanent fossil sites are protected by the Nature Conservation Law, either as Nature Reserve or as Monument of Nature. This legislation alone cannot provide absolute protection, but gives a framework on the status of fossils and the rights and obligations of all whose activities concern fossils. Furthermore, the legislation provides the state’s support in the case of conflict. Actually, conflicts are rare; under the provisions of the law a sense of trust and co-operation has developed. The public benefits from a great number of outstanding finds made possible by the regulations since 1972.